Pancasila dan nilai agama: Tinjauan perilaku bunuh diri dalam pandangan Islam, masyarakat dan Pancasila - Qolby, Nurlatifatul; Fawwaz, Ibnatia Hasna; Caereny, Fajaricha Aurera (Maliki Interdisciplinary Journal, 2024)
All living things, including humans, experience the cycle of life. From birth, born into the world, and continue to live there until humans die or die. Death is an unavoidable fact between the stages of human life. In islam, a believer believes that death occurs, cannot be avoided, requested, proposed, or postponed. In the media, some cases show some individuals deliberately hastening their deaths by committing suicide or euthanasia. However, people who are muslims should be grateful for allah's perfect creation. At-tin). This is because islam is a religion of rights, which regulates all kinds of problems of human life with various legal concepts and social values. This concept is taught to humans to practice so that they are happy in this world and in the hereafter. Similarly, pancasila whose implementation includes principles of life and laws for all acts of behavior.